African Perspectives on South–South Migration (Routledge Studies on African and Black Diaspora, 2024)
This book investigates the diverse and dynamic forms of migration within Africa. Centring themes of agency, resource flows, and transnational networks, the book examines the enduring appeal of the Global South as a place of origin, transit, and destination. Popular media, government pronouncements, and much of the global research discourse continue to be oriented towards migration from the Global South to the Global North, despite the fact that the vast majority of migration is South-South. This book moves beyond these mischaracterisations and instead distinctly focuses on the agency of African migrants and the creative strategies they employ while planning their routes within and across the African continent. Case studies explore the flow of resources such as people, money, skills, and knowledge throughout the continent, while also casting a light on the lived experiences of migrants as they negotiate their sometimes precarious and vulnerable positions. Underpinned by intensive empirical studies, this book challenges prevailing narratives and provides a new way of thinking about South-South Migration. Composed by a majority of scholars from the Global South, the book will be crucial reading for researchers, students, and policy makers with a focus on South-South Migration, Migration and Inequalities, Migration and Development, and Refugee and Humanitarian Studies.